Education and Worklife in Times of Uncertainty: Challenges Emerging from the COVID-19 Pandemic in the Field of Sustainable Development - Monferrer, Diego; Rodríguez Sánchez, Alma; Estrada-Guillén, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
On 11 March 2020, the World Health Organisation declared novel coronavirus (SARS-CoV-2) an unprecedented global pandemic. Nearly every country across the globe is struggling to reduce the spread of the COVID-19 virus and to limit its health, societal and economic consequences. As a response to that, with almost immediate effect, students, teachers and workers in general and across the globe were thrown into a new scenario of online work and education. In the midst of this emotional climate laden with fear, uncertainty, sadness and anxiety, millions of students all over the world were confined to their homes and the entire educational community had to adapt to a distance education model. The same occured with workers of different disciplines; they have to balance work and life in the same place. Therefore, homes suddenly became schools, universities and workplaces all at the same time. Against this backdrop, this Special Issue focuses on the study, evaluation and analysis of the opportunities the pandemic offers in three related aspects: first, for building an education for sustainable development. Second, for creating decent working conditions. Finally, to enhance health and well-being both at the workplace and at home. Authors from a range of disciplines, such as education, psychology, management, social sciences and other areas related to sustainable development, have contributed with differrent manuscripts. They address the challenges of studying, working and living in times of uncertainty in order to build sustainable development in those areas from theoretical and applied research.